2016
DOI: 10.1080/09540121.2016.1139038
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health and HIV transmission among female sex workers: a systematic review and meta-analysis

Abstract: Current HIV prevention interventions for female sex workers (FSWs) have tended to target the cognitive factors in changing their behaviors, yet little attention has been paid to the psychological factors that influence the behavior of women in sex work. This review aimed to explore the associations between the psychological health of FSWs and HIV risk. A total of eight studies published in English before July 2013 were identified and reviewed. FSWs had reported psychological issues, including depression, suici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 44 publications
1
18
2
9
Order By: Relevance
“…Contrary to previous evidence on sexual risk taking among women in sex work (Yuen et al, 2016), we found no statistically significant association with depressive symptoms. However, women in the high-risk group for depression reported more unprotected sex acts (32% vs. 19%) and more overall number of sex acts (89 vs. 61) with a paying partner in the last 3 months, suggesting important clinical significance for sexual risk.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to previous evidence on sexual risk taking among women in sex work (Yuen et al, 2016), we found no statistically significant association with depressive symptoms. However, women in the high-risk group for depression reported more unprotected sex acts (32% vs. 19%) and more overall number of sex acts (89 vs. 61) with a paying partner in the last 3 months, suggesting important clinical significance for sexual risk.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the elevated percentage of women at risk for depression from the current study is consistent with other samples of women in sex work conducted elsewhere in Asia; about 53.9% in Hong Kong (Lau et al, 2010), 62.0% in China (Hong et al, 2007), 82.4% in Nepal (Sagtani et al, 2013), and 86% in India (Suresh et al, 2009) had depression or depressive symptoms. A recently-published systematic review on the psychological health of female sex workers globally reported a pooled prevalence of probable depression to be 62.4% (Yuen et al, 2016), nearly equivalent with the findings of this study. None of these studies (in Mongolia or elsewhere), however, utilized the BSI subscale on depressive symptoms, making direct comparisons difficult.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A systematic review pertaining to the psychological health of women working in sex work globally reported the prevalence of depression at 62.4%. This systematic review also found a significant association between depression and sexual risk taking in four out of five studies included in the review (Yuen et al, 2016). The relationship between depression and HIV risk is more typically mediated by other HIV risk behaviors, including alcohol use.…”
Section: Introductionmentioning
confidence: 64%
“…Psychological distress can be defined as negative feelings about oneself or one’s situation, such as feelings of depression, hopelessness and worthlessness (Kessler et al 2002; Radloff 1977). Psychological distress, particularly depression, is highly associated with increased HIV risk behaviours such as inconsistent condom use (Devieux et al 2015; Kennedy et al 1993; Yuen et al 2016). Researchers (Villegas et al 2013; Villegas-Rodriguez et al 2011) conducted a sexual risk reduction randomised controlled trial with 548 Hispanic women and found self-esteem and HIV knowledge to be significant predictors of self-efficacy for HIV prevention.…”
Section: Introductionmentioning
confidence: 99%